Weaning Age Affects the Development of the Ruminal Bacterial and Archaeal Community in Hu Lambs During Early Life - Mao, Huiling; Zhang, Yanfang; Yun, Yan; Ji, Wenwen; Jin, Zhao; Wang, Chong; Yu, Zhongtang (Frontiers in Microbiology, 2021)
Weaning plays an important role in many animal processes, including the development of the rumen microbiota in ruminants. Attaining a better understanding of the development of the rumen microbial community at different weaning stages can aid the identification of the optimal weaning age. We investigated the effects of weaning age on ruminal bacterial and archaeal communities in Hu lambs. Thirty male Hu lambs were randomly assigned to two weaning-age groups: a group weaned at 30 d of age (W30) and a group weaned at 45 d of age (W45), with each group having 5 replicate pens. On the weaning day (d 30 for W30 and d 45 for W45) and at five days postweaning ( d 35 for W30 (PW30) and d 50 for W45 (PW45)), one lamb from each replicate was randomly selected and sacrificed. Rumen contents were collected to examine the ruminal microbiota. Compared to W30, PW30 had a decreased relative abundance of Bacteroidetes. At genus level, the extended milk replacer feeding (W45 vs. W30) increased the relative abundance of Ruminococcus while decreased that of Prevotella and Dialister. Compared to W30, PW30 exhibited decreased relative abundances of Prevotella, Dialister and Bacteroides but an increased unclassified Coriobacteriaceae. No significant difference was noted in the detected archaeal taxa among the animals. The function "biosynthesis of secondary metabolites" was less predominant in PW30 than in W30, whereas the opposite held true for "metabolism of cofactors and vitamins". Some bacterial genera were significantly correlated with rumen volatile fatty acid (VFA) concentration or other animal measures, including negative correlations between ruminal VFA concentration and unclassified Mogibacteriaceae and unclassified Veillonellaceae; positive correlations of ruminal papillae length with Fibrobacter and unclassified Lachnospiraceae, but negative correlations with Mitsuokella and Succiniclasticum; and negative correlations between plasma D-lactate concentration and Prevotella, unclassified Paraprevotellaceae, and Desulfovibrio. Our results revealed that the ruminal bacterial community underwent larger changes over time in lambs weaned at 30 d of age than in lambs weaned half a month later. Thus, extending milk replacer feeding to 45 days weaning was recommended from the perspective of the rumen microbial community in the Hu lamb industry.